1977
DOI: 10.1210/jcem-44-2-346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Calcitonin Therapy on the Clinical Course of Osteogenesis Imperfecta

Abstract: 10 children with osteogenesis imperfecta, 4 with "tarda" and 6 with "congenita" varieties of the disease, were treated with salmon calcitonin (SCT) for intervals ranging from 14 to 35 months. Responses to SCT therapy in patients with osteogenesis imperfecta tarda were characterized by an apparent decreased fracture incidence in three, a fall in either alkaline or acid phosphatase, and a rate of increase in forearm bone mass which was greater than that observed in an untreated "tarda" population. The chemical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1
1

Year Published

1979
1979
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 41 publications
1
8
1
1
Order By: Relevance
“…In the present study, where the BMC values were used to determine any change in bone mass during the treatment period, only two patients revealed a significant reduction in BMC. In disagreement with Rosenberg et al (1977), we found no changes in BMC during calcitonin therapy.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…In the present study, where the BMC values were used to determine any change in bone mass during the treatment period, only two patients revealed a significant reduction in BMC. In disagreement with Rosenberg et al (1977), we found no changes in BMC during calcitonin therapy.…”
Section: Discussioncontrasting
confidence: 97%
“…Like others (Castells et al 1972,19761, we found no changes in serum calcium or phosphorus concentrations during treatment. Rosenberg et al (1977) found that long-term therapy with salmon calcitonin resulted in serum values for calcium and phosphorus which in most cases were lower than the pre-treatment values. In our study the 24-h excretion of hydroxyproline was normal, but at the end of the treatment period a slight increase in the hydroxyproline excretion was noted.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Osteogenesis imperfecta is an infrequent generalized disease in bone and connective tissue characterized by increased bone resorption, osteopenia and spontaneous fractures (Rosenberg et al 1977). Both short-term and long-term studies of calcitonin treatment have suggested an improvement in bone changes in patients with osteogenesis imperfecta tarda (Rosenberg et al 1977, Castells et al 1972.…”
mentioning
confidence: 99%